Implementasi Kebijakan Pemerintah Daerah Dalam Perda No. 5 Tahun 2016 Tentang Pengelolaan Usaha Perkebunan Kelapa Sawit di Kabupaten Barito Kuala Kalimantan Selatan - Muna Havid (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Regional regulation (Perda) number 5 of 2016 in Barito Kuala Regency specifically regulates the management of oil palm plantation businesses which are the main plantation products in Indonesia and have a major influence on the regional and national economy. The implementation of this policy is crucial because it is directly related to environmental sustainability, business governance, and the welfare of local residents. This study aims to examine the Implementation of the Regional Government Policy of Barito Kuala Regency through Regional Regulation Number 5 of 2016 concerning Management of Oil Palm Plantation Businesses. The results of the study indicate that the policy has provided a direction for sustainable management, but its implementation faces a number of obstacles such as limited supervision, administrative obstacles, and land conflicts. Regional Regulations play an important role in organizing oil palm businesses that support community welfare while maintaining environmental sustainability.